Tantangan Oikumene di Asia: Sebuah Kajian Kontekstual - Yersi Hotmauli Berutu; Meditatio Situmorang (Publisher STPKat, 2024)
Asia as the largest continent with a vast diversity of cultures, religions, and ethnicities presents a unique challenge for the ecumenical movement, which seeks to build unity among Christian churches. the ecumenical movement, which seeks to build unity among Christian churches in the spirit of the unity of faith. in the spirit of the unity of faith. This article examines the various challenges challenges facing the ecumenical movement in Asia, including religious pluralism, different theology, political dynamics, and socio-economic contexts. An understanding of these challenges is important to encourage cross-cultural dialogue and strengthen the witness of the church in Asia. witness of the church in Asia. The challenges of ecumenism in Asia reflect the complexity of religious life in the region. religious life in the region. However, through inclusive dialog, education, and cooperation inclusive cooperation. The ecumenical movement in Asia is not only about the internal unity of the church, but also about contributing to peace and cooperation. unity of the church, but also about contributing to peace and justice in an increasingly complex world. justice in an increasingly complex world.